Hadis-Hadis Wabah Taun dalam Fatwa Mui Nomor 14 Tahun 2020: (Studi Ma’ani Al-Hadits) - Mustawa, Mustawa; Yuslem, Nawir; Damanik, Nurliana (Kamaya: Jurnal Ilmu Agama, 2023)
MUI Fatwa Number 14 of 2020 regarding the epidemic this year there are still many pros and cons among the public. The public doubted and rejected the fatwa. The reason is because people doubt the accuracy of the arguments used, especially the hadiths contained in them. This research aims to understand the meaning of hadiths about the year's epidemic and their relevance to the COVID-19 outbreak. The research uses library research using data collection techniques using takhrij al-hadith, i'tibar al-sanad, naqd al-matan, and fiqh al-hadith. After the data was collected, data analysis was carried out using an inductive method which refers to three procedures, namely analysis of the matan test, providing conclusions on the status of the validity of the hadith and analysis of the understanding of the hadith. This research found that the hadith contained in MUI fatwa Number 14 of 2020 can be used as hujjah (maqbul). The meaning of these hadiths is relevant to preventing the COVID-19 outbreak which then has preventive steps in dealing with the outbreak. The Prophet's recommendation to carry out quarantine for those infected with the plague, means that there is separation between infected people and healthy people. The values of handling this year's outbreak can be applied in Indonesia based on Law No. 6 of 2018 concerning Health Quarantine.